ESTIMATION OF LIPID PROFILE IN VARIOUS GRADES OF NON ALCOHOLIC FATTY LIVER DISEASE DIAGNOSED ON ULTRASONOGRAPHY - ALLAMSETTY SANTOSHINI; PESARKAYALA SWATHI; SAJJA RAVINDRA BABU; RANJIT NAIR (International Journal of Pharma and Bio Sciences, 2016)
Non alcoholic fatty liver disease (NAFLD) is the accumulation of excess fat in the liver of people who drink little or no alcohol. It is a common disorder and for most people, causes no signs and symptoms. Objective behind the study was to compare lipid profile in different grades of Non-alcoholic fatty liver disease (NAFLD) diagnosed on ultrasonography. A cross sectional study of 165 subjects which included 97 males and 68 females was conducted. The subjects were categorized as having altered lipid profile (total cholesterol, AST, ALT, triglycerides) abnormal liver enzymes, different grades of NAFLD and Body mass index. Ultrasonography which is non-invasive, painless, simple tool compared to liver biopsy for diagnosis of NAFLD was discussed.